2018
DOI: 10.1186/s12882-018-0920-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of protein- energy wasting among patients with chronic kidney disease at Mulago hospital, Kampala-Uganda: a cross-sectional study

Abstract: BackgroundChronic kidney disease (CKD) is global health concern and priority. It is the 12th leading cause of death worldwide. Protein Energy Wasting occurs in 20–25% of patients with chronic kidney disease and can lead to a high morbidity and mortality rate. We determined the prevalence of protein energy wasting and factors associated among patients with chronic kidney disease at Mulago National Referral Hospital, Kampala, Uganda.MethodsWe conducted a cross-sectional study recruiting 182 (89 non-CKD patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 11 publications
1
22
0
2
Order By: Relevance
“…18 However, the prevalence of PEW reported in both studies for Ethiopian CKD patients is much lower than what was reported from Mulago hospital, Kampala-Uganda which shows that the prevalence of PEW among CKD patients was 44%. 16 This difference might be due to geographical and lifestyle variations among populations included in the study.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…18 However, the prevalence of PEW reported in both studies for Ethiopian CKD patients is much lower than what was reported from Mulago hospital, Kampala-Uganda which shows that the prevalence of PEW among CKD patients was 44%. 16 This difference might be due to geographical and lifestyle variations among populations included in the study.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is similar to the Ugandan study which reported that the stage of CKD was associated with PEW; especially CKD patients with stage 4 were 6.4 times more likely to develop PEW compared to stage 1 CKD. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has a bearing on reducing post-caesarean sepsis. Conversely catholic faith is liberal about alcohol consumption and this may have an implication on the risk of post-caesarean wound sepsis among the catholic mothers [35].…”
Section: Risk Factors Of Post Caesarean Wound Sepsis Among Mothers Atmentioning
confidence: 99%
“…El estudio EQUAL (European Quality Study on treatment in advanced chronic kidney disease), un estudio internacional, que valoro paciente en estadio renal 3 y Namuyimbwa et al (2018) indica en un estudio de Uganda que la prevalencia de la DPE en pacientes con ERC, en estados tanto predialíticos como dialíticos, es importante y su tamizaje y control reduce la morbimortalidad (11) .…”
Section: Prevalenciaunclassified